Emerging Gender Regimes and Policies for Gender Equality in a Wider Europe - Pascall, Gillian; Lewis, Jane (Cambridge University Press, 2004)
This article addresses some implications for gender equality and gender policy at European and national levels of transformations in family, economy and polity, which challenge gender regimes across Europe. Women’s labour market participation in the west and the collapse of communism in the east have undermined the systems and assumptions of western male breadwinner and dual worker models of central and eastern Europe. Political reworking of the work/welfare relationship into active welfare has individualised responsibility. Individualisation is a key trend west − and in some respects east − and challenges the structures that supported care in state and family. The links that joined men to women, cash to care, incomes to carers have all been fractured. The article will argue that care work and unpaid care workers are both casualties of these developments. Social, political and economic changes have not been matched by the development of new gender models at the national level. And while EU gender policy has been admired as the most innovative aspect of its social policy, gender equality is far from achieved: women’s incomes across Europe are well below men’s; policies for supporting unpaid care work have developed modestly compared with labour market activation policies.Enlargement brings new challenges as it draws together gender regimes with contrasting histories and trajectories. The article will map social policies for gender equality across the key elements of gender regimes – paid work, care work, income, time and voice – and discuss the nature of a model of gender equality that would bring gender equality across these. It analyses ideas about a dual earner–dual carer model, in the Dutch combination scenario and ‘universal caregiver’ models, at household and civil society levels. These offer a starting point for a model in which paid and unpaid work are equally valued and equally shared between men and women, but we argue that a citizenship model, in which paid and unpaid work obligations are underpinned by social rights, is more likely to achieve gender equality.